Development of E-Worksheet Based on Flipped-Guided Inquiry Learning (FGIL) in Thermochemistry for Phase F - Defista, Chesa; Aznam, Nurfina (Universitas Pendidikan Ganesha, 2024)
Thermochemistry has abstract and mathematical material which makes it difficult for students to understand this material. Students are required to discuss this material in depth so teaching materials are needed that support student learning flexibly. Thus, the research purpose is to develop a thermochemistry e-worksheet based on FGIL for high school students in phase F. The research type is R&D with the ADDIE model which is limited to the Development stage. Content validity was carried out with four validators and practicality was obtained from 36 phases F high school students. The research instruments were validation sheets and student response questionnaires. The validity value is determined by Aiken's V test, if the V value is > 0.40 then an aspect is declared valid. The research findings demonstrated that the average assessment on the material aspect was 0.92 (very valid); the media aspect 0.96 (very valid); and the language aspect was 0.83 (very valid), while the average percentage of student responses was 96% (very practical). So, it can be said that the developed thermochemistry e-worksheet based on FGIL is valid and practical to use.